2006
DOI: 10.1063/1.2338364
|View full text |Cite
|
Sign up to set email alerts
|

Search for fusion suppression in reactions having entrance-channel mass-asymmetry values around the Businaro-Gallone point

Abstract: Available data on evaporation residue (ER) production and fission in a wide region of compound nucleus (CN) masses and entrance-channel mass-asymmetry values have been analyzed in search for the "starting point", where the fusion suppression due to the quasi-fission (QF) effect starts to show up. Comparing cross sections for the ER production and fission in reactions leading to the same CN, but having different values of entrance-channel mass-asymmetry, one can extract the fusion probability for a more symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…They have used a shellcorrected fission barrier while we have used FRLDM barrier which is lower. Consequently, our ER cross-sections are smaller than that found in [16], which means a higher value of best-fit K f in our case. Further, we included the shell-correction in level density parameter which was taken from the work of Ignatyuk et al [17].…”
Section: Statistical Model Calculationscontrasting
confidence: 40%
See 1 more Smart Citation
“…They have used a shellcorrected fission barrier while we have used FRLDM barrier which is lower. Consequently, our ER cross-sections are smaller than that found in [16], which means a higher value of best-fit K f in our case. Further, we included the shell-correction in level density parameter which was taken from the work of Ignatyuk et al [17].…”
Section: Statistical Model Calculationscontrasting
confidence: 40%
“…We found an energy dependence of K f as we fitted the individual data point and the best-fitted K f value 0.8 lies between the dispersion of K f ( 0.6-1.0) values. It is to be noted that in another recent calculation by Sagaidak et al [16], best-fit value of K f is reported to be 0.8 at higher excitation energies. Our results show a better fit at K f = 0.8 for lower excitation energies.…”
Section: Statistical Model Calculationsmentioning
confidence: 99%
“…Some of the systems studied in this work have been studied previously, i.e., the reaction of 18 O with 197 Au [25,32,55]. In [32], the fragment angular distributions were measured for the reaction of 78-97 MeV 18 O with 197 Au.…”
Section: This Papermentioning
confidence: 99%
“…A number of calculations of P CN for cold fusion reactions have been made using the "fusion by diffusion" approach [5,[44][45][46] that differ from both the DNS and Zagrebaev and Greiner approaches. There have also been a number of attempts [25,44,46,47] to make semi-empirical estimates of P CN using one or another models for σ capture , W sur and using measured values for σ EVR to get values of P CN for both hot and cold fusion reactions. Other aspects of quasifission , such as the time scale and the role of deformation effects in the entrance channel have been treated [38,[48][49][50].…”
Section: B Reaction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation